BIOREMEDIATION OF A PETROLEUM-HYDROCARBON POLLUTED AGRICULTURAL SOIL AT VARIOUS LEVELS OF SOIL TILLAGE IN PORTHARCOURT, NIGERIA (Nigerian Journal of Technology, 2006)
A combination of field cells involving a control and five treatment cells were evaluated under field conditions in the bioremediation of a petroleum- hydrocarbon polluted agricultural soil over a six-week period. Previous works have indicated that crude oil contamination of soils depletes oxygen reserves in the soils and slows down its diffusion rate to the deeper layers. Hence, this hypothesis was tested in the study by the treatments employed. The treatment option used was the application of mineral fertilizer, and different rates of oxygen exposure through various levels of soil tillage. In the experiments described in this paper, conditions of a major spill were simulated by sprinkling crude oil on the cells using perforated cans. The treatment applications were then resorted to and relevant soil physicochemical characteristics monitored at intervals. The results of the study showed an enormous increase in total heterotrophic bacterial (THB) counts in all the treatment cells. The percentage reduction in total hydrocarbon content (88% to 99%) experienced in the cells that received treatment were significantly different from the control. These results highlight the view that the availability of large amounts of oxygen in the soil profile induces an accelerated biodegradation of petroleum hydrocarbons in a polluted agricultural soil and implies that regular tillage of contaminated soils in the presence of nutrients could achieve the decontamination of such soils.